Pengembangan Karir Dalam Rangka Penempatan Jabatan pada Dinas Tenaga Kerja dan Perindustrian Kota Kendari - Alfin Yunika; Aminuddin Aminuddin; Justawan Justawan (REZ PUBLICA : Jurnal Administrasi Negara, Politik-Pemerintahan & Hubungan Internasional, 2021)
This study aims to determine career development in the context of job placement and to determine position placement at the Kendari City Manpower and Industry Office. The method used in this research is descriptive qualitative research method. Data collection technique es were carried out by means of library research and field research using interview, documentation, and interview methods. The results showed that the career development of employees through education and training at the Department of Manpower and Industry of Kendari City had not been carried out optimally, most of the employees who had met the training requirements but had not yet had the opportunity to take part in the training so that from the aspect of implementing the training it had not been effective. , then the placement of positions is more focused on the placement of vacant positions, while in terms of educational background it has not been a concern due to family factors and proximity factors.